Tamoxifen is better than low-dose clomiphene or gonadotropins in women with thin endometrium (<7 mm) after clomiphene in intrauterine insemination cycles: A prospective study - Sunita Sharma; Geetha Rani; Gunja Bose; Indranil Saha; Sikha Bathwal; B N Chakravarty (Wolters Kluwer Medknow Publications, 2018)
Aim: Gonadotropin stimulation is used as the second line of treatment in patients with thin endometrium following clomiphene citrate (CC) administration, which is associated with higher cost, multiple births, and ovarian hyperstimulation syndrome. Tamoxifen (TMX), a selective estrogen receptor modulator, acts as an agonist on the endometrium. The objective of the present study was to compare the efficacy of low-dose CC, TMX, and gonadotropins in women with thin endometrium (<7 mm) following Clomiphene in intrauterine insemination (IUI) cycles. Settings and Design: A prospective observational study between December 2011 and June 2013 was carried out in a tertiary infertility center. Methods: Women (n = 502) undergoing IUI with endometrium <7 mm after 100 mg CC were included in the study and divided into three treatment groups. Women in Group A (n = 182, cycles = 364) received clomiphene (50 mg/day from day 3 to 7), Group B (n = 179, cycles = 342) received TMX (40 mg/day from day 3 to 7), and Group C (n = 141, cycles = 226) received continuous urine-derived follicle-stimulating hormone 75-150 IU from day 3 onward until human chorionic gonadotropin injection. Endometrial thickness (ET), pregnancy rate, and live birth rate were considered as main outcome measures. Statistical Analysis: Multiple comparisons using one-way ANOVA and Schiff's test were performed. Results: Pregnancy and live birth rate were significantly higher (P < 0.004) in TMX and gonadotropin groups compared to clomiphene. A number of follicles in the TMX group were found to be lower (P < 0.001) compared to other two groups. In polycystic ovary syndrome patients, ovulation induction with TMX resulted in inadequate response in more than half of the cycles. Conclusions: TMX can improve ET and live birth rate in patients with thin endometrium after clomiphene.